ANALISIS PERATURAN MAHKAMAH AGUNG NO. 02 TAHUN 2012 PADA TAHAP PENYIDIKAN DI KEPOLISIAN TERHADAP TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN (STUDI DI WILAYAH HUKUM POLRES LANGKAT) - Rosyid Hartanto (USU LAW JOURNAL, 2016)
ABSTRACT Efforts and policies to create a good rule of criminal law in essence can not be separated from the purpose of crime prevention. Likewise regulations issued by the Supreme Court regarding the misdemeanor (Tipiring), namely: the Supreme Court Regulation No. 2 of 2012 on Limitation Adjustment light crime and the amount of penalties in the Criminal Code. Related to this research that addresses the crime of theft by weighting, then the crime of theft under $ value. 2.500.000, - (Two Million Five Hundred Thousand) can not be detained. The background to the Supreme Court Regulation No. 2 In 2012, the efforts to provide justice to the people, especially in settling disputes-minor criminal cases (Tipiring). Technically law called the Tipiring is a criminal offense punishable by imprisonment or a maximum of three months imprisonment and or a fine of up to Rp. 7.500, - (Seven Thousand Five Hundred Rupiah) and a mild insult. Therefore, the substance, the Supreme Court Regulation No. 2 of 2012 was actually not on the value of rupiah, but the crimes are legal threat than 3 (three) months and it is not required to be retained. In the Supreme Court Regulation No. 2 In 2012, Article 1, explained that the words Rp. 250, - (Two Hundred and Fifty Rupiah) in Article 364, 373, 379, 384, 407 and 482 of the Penal Code read as Rp. 2.500.000, - (Two Million Five Hundred Thousand). Later, in Article 2 paragraph (2) and (3) is described, if the value of the goods or the money is not worth more than 2.5 million dollars President of the Court immediately set the Single Judge to examine, hear and decide the case with the Fast Interrogation under Article 205-210 Criminal Procedure Code and the President of the Court do not provide for the detention or extension of detention. Keywords : Supreme Court, Limitation Adjustment, theft by weighting